2011
DOI: 10.54207/bsmps1000-2011-1ra9m0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variation of Poplar Clones under Sub-Tropical and Sub-Temperate Conditions

Abstract: Clonal variation in morphological growth parameters of Populus deltoides and P. ciliata were studied in the nursery stages in Sub-tropical (Naganji) and Sub-temperate (Shilli) regions to assess their planting success and growth potential in their climatic zones. P. deltoides clones planted in Sub-tropical nursery recorded highest average height (298.70cm), basal diameter (21.75mm) and leaf area (175.40cm2) with clone ‘PD-1’ sharing maximum height (350.00± 26.07cm) and leaf area (193.70±6.86cm2). Whereas, basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Growth parameters of Populus deltoides and P. ciliata clones were studied in sub-tropical (Naganji) and sub-temperate (Shilli) nurseries and found significant differences among clones for plant height, basal diameter and volume index [5]. Similarly, superior Populus deltoides clones were screened in the nursery by Sharma et al [6] and found 23 clones in plant height and volume index and 22 clones in basal diameter significantly different against check clone G-48.…”
Section: Resultsmentioning
confidence: 99%
“…Growth parameters of Populus deltoides and P. ciliata clones were studied in sub-tropical (Naganji) and sub-temperate (Shilli) nurseries and found significant differences among clones for plant height, basal diameter and volume index [5]. Similarly, superior Populus deltoides clones were screened in the nursery by Sharma et al [6] and found 23 clones in plant height and volume index and 22 clones in basal diameter significantly different against check clone G-48.…”
Section: Resultsmentioning
confidence: 99%